Bochner curvature tensor of Almost Kahler manifold - Jawad, Jassim (University of Thi-Qar Journal of Science, 2010)
In this paper we study the Bochner curvature tensor of almost Kahler manifold. We foundthe components of Bochner tensor of almost Kahler manifold in the adjoint G-structure space byusing Kirichenko's tensors. It has been proved that an almost Kahler manifold is a manifold ofclass if and only if it is Kahler.